2012
DOI: 10.1038/jcbfm.2012.60
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of Cholinergic Denervation in Parkinson's Disease without Dementia

Abstract: Parkinson's disease (PD) is a multisystem neurodegenerative disorder. Heterogeneous clinical features may reflect heterogeneous changes in different brain regions. In contrast to the pronounced nigrostriatal denervation characteristic of PD, cholinergic changes are less marked. We investigated cholinergic innervation activity in PD subjects relative to normal subjects. Nondemented PD subjects (n = 101, age 65.3±7.2 years) and normal subjects (n = 29, age 66.8 ± 10.9 years) underwent clinical assessment and [ 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
173
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 162 publications
(189 citation statements)
references
References 44 publications
7
173
1
Order By: Relevance
“…Subjects with PDD have a more profound reduction of ACh markers in the brain than those with PD or AD79 and the pathological changes seen at postmortem are supported by nuclear medicine studies 80 81. Poor attention at baseline and the PIGD phenotype are independent predictors of cognitive decline in PD82 and ACh deficiency is proposed as the unifying link 7.…”
Section: Linking Neurotransmitter Changes and Cognitive Dysfunctionmentioning
confidence: 90%
See 1 more Smart Citation
“…Subjects with PDD have a more profound reduction of ACh markers in the brain than those with PD or AD79 and the pathological changes seen at postmortem are supported by nuclear medicine studies 80 81. Poor attention at baseline and the PIGD phenotype are independent predictors of cognitive decline in PD82 and ACh deficiency is proposed as the unifying link 7.…”
Section: Linking Neurotransmitter Changes and Cognitive Dysfunctionmentioning
confidence: 90%
“…Poor attention at baseline and the PIGD phenotype are independent predictors of cognitive decline in PD82 and ACh deficiency is proposed as the unifying link 7. At least initially, PPN degeneration with subsequent reduction of ACh in the thalamus and brainstem could contribute to gait disturbance and falls whereas nbM degeneration and subsequent reduction of ACh in the DLPC could be the driver of attentional deficit, as supported to some extent by positron emission tomography (PET) studies 80. However, this is likely to be too simplistic given the heterogeneous pathological process occurring in every individual with PD.…”
Section: Linking Neurotransmitter Changes and Cognitive Dysfunctionmentioning
confidence: 99%
“…The executive dysfunction seen in early PD has been attributed to striatal dopaminergic degeneration, particularly in the caudate nucleus [10, 11]. However, the cholinergic system also plays a significant role in PD cognitive impairment, especially when dementia develops [12, 13]. The use of the MoCA to define PD-MCI has not been well investigated using combined neurochemical and detailed neuropsychological testing.…”
Section: Introductionmentioning
confidence: 99%
“…It is now evident that there are mild subclinical cognitive deficits in ET patients (Louis 2010;Lacritz et al 2002;Sahin et al 2006;Balaban et al 2012;Benito-León and Louis 2011;Kim et al 2010), especially in attentional and executive functions (Tröster et al 2002). The cognitive dysfunction in ET and PD patients (Gasparini et al 2001;Higginson et al 2008) is comparable, pointing to a common dysregulation of both dopamine and cholinergic pathways (Bohnen et al 2012). Neuroimaging studies in ET patients showed grey matter changes in several areas including bilateral cerebellum, parietal lobes, and right frontal lobe (Benito-León et al 2009).…”
Section: Introductionmentioning
confidence: 94%